A three-dimensional lattice Boltzmann model for numerical investigation of bubble growth in pool boiling. (December 2016) - Sadeghi, Reza; Shadloo, Mostafa Safdari; Jamalabadi, Mohammad Yaghoub Abdollahzadeh; Karimipour, Arash
Abstract: In this paper, a three-dimensional lattice Boltzmann model is proposed to simulate pool-boiling phenomena at high-density ratios. The present model is able to predict the temperature field inside the bubble. The three-dimensional multiphase model is validated against the analytical solution of evaporation d 2 law problem and Laplace's law. In addition, effects of different parameters including, Jacob number, gravitational acceleration ( g ) and surface tension ( σ ) on bubble departure diameter are presented for further validation. The bubble departure diameter is found to be proportional to g − 0.354 and σ 0.5, and has a linear relation with Jacob number. These results are more consistent with previous experimental correlations when compared with available lattice Boltzmann literature. Furthermore, the dynamic behavior of multiple bubble formation sites such as micro convection and vortex ring mechanism are presented to show the capability of presented model for capturing more complex physical phenomena. To sum up, the proposed three-dimensional lattice Boltzmann model is feasible and accurate for numerical simulations of pool boiling.